Effect of kaolin clay and alumina on thermal performance and char morphology of intumescent fire retardant coating - Aziz, H. (EDP Sciences, 2014)
Intumescent fire retardant coating (IFRC) have been developed by using ammonium polyphosphate, expandable graphite, melamine, boric acid, kaolin clay and alumina as fillers bound together with epoxy resin and cured with the help of curing agent. Five different formulations were developed with and without using fillers. Cured samples were burned in furnace at 500Â°C for 2h for char expansion. Bunsen burner test was performed for 1h using UL-94 vertical burning test to investigate the thermal performance of IFRC. The resultant char obtained after burning of coated samples were characterized by using field emission scanning electron microscopy for char morphology. Char composition was analyzed by using fourier transform infrared spectroscopy. Thermogravimetric analysis was carried out to investigate the residual weight of coating. Results showed that formulation with 0.5 weight of kaolin clay and 0.5 weight of alumina provide best thermal performance, uniform and multi-porous char structure with high anti-oxidation property. Â© 2014 Owned by the authors, published by EDP Sciences.